Overview of Triglyceride Levels and Estimated VLDL in Atherosclerosis Development among Patients over 50 Years - Mohamad Zaul Haq; Bekti Mastiadji; Subur Wibowo (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Atherosclerosis is a chronic arterial disease caused by disorders of lipid metabolism, leading to the formation of atherosclerotic plaques. Elevated triglyceride levels are associated with increased production of Very Low-Density Lip oprotein (VLDL), which plays an important role in the process of atherogenesis and contributes to an increased risk of cardiovascular disease. Therefore, the measurement of triglyceride levels and the estimation of VLDL are important for the early detection of atherosclerosis risk, particularly in patients aged over 50 years. This study aimed to describe triglyceride levels and VLDL estimation in relation to atherosclerosis formation among patients aged over 50 years at QIM Batang Hospital. This study employed a descriptive research design involving 27 patients aged over 50 years. Triglyceride levels were measured using the enzymatic colorimetric GPO-PAP method with a chemistry analyzer, while VLDL levels were estimated using the Friedewald formula (VLDL = triglycerides/5). Data were analyzed descriptively and presented as frequency distributions and percentages. The laboratory results showed that normal triglyceride levels were found in 10 respondents (37.04%), borderline-high triglyceride levels in 10 respondents (37.04%), and high triglyceride levels in 7 respondents (25.92%). High estimated VLDL levels were observed in 17 respondents (62.96%), whereas normal estimated VLDL levels were found in 10 respondents (37.04%). These findings indicate that most patients aged over 50 years had elevated estimated VLDL levels, suggesting a potential increase in the risk of atherosclerosis development.